Atom probe tomography analysis of possible rhenium clustering in nickel-based superalloys - Mottura, A; Miller, M; Reed, R (2008)
A local electrode atom probe is used to characterise a number of binary and commercial nickel-based alloys, specifically to determine whether rhenium atoms form solute clusters in these materials. The data are analysed via a statistical approach and results are compared to simulations which take the typical efficiency of the atom probe and the scatter in atomic positions into account. Thus, even the smallest clusters can - in principle - be detected by the algorithm. The analysis demonstrates conclusively that rhenium is not prone to clustering in the nickel lattice above the level associated with the random distribution of Re atoms. A similar conclusion applies to the other 5d elements (Ta, W, Ir and Pt) analysed in this study.